Effects of n−3 Polyunsaturated Fatty Acids on Cardiac Ion Channels - Moreno, Cristina; Macias, Alvaro; Prieto, Angela; de la Cruz, Alicia; Gonzalez, Teresa; Valenzuela, Carmen (Frontiers in Physiology, 2012)
Dietary n−3 polyunsaturated fatty acids (PUFAs) have been reported to exhibit antiarrhythmic properties, and these effects have been attributed to their capability to modulate ion channels. In the present review, we will focus on the effects of PUFAs on a cardiac sodium channel (Nav1.5) and two potassium channels involved in cardiac atrial and ventricular repolarization (Kv) (Kv1.5 and Kv11.1). n−3 PUFAs of marine (docosahexaenoic, DHA and eicosapentaenoic acid, EPA) and plant origin (alpha-linolenic acid, ALA) block Kv1.5 and Kv11.1 channels at physiological concentrations. Moreover, DHA and EPA decrease the expression levels of Kv1.5, whereas ALA does not. DHA and EPA also decrease the magnitude of the currents elicited by the activation of Nav1.5 and calcium channels. These effects on sodium and calcium channels should theoretically shorten the cardiac action potential duration (APD), whereas the blocking actions of n−3 PUFAs on Kv channels would be expected to produce a lengthening of cardiac action potential. Indeed, the effects of n−3 PUFAs on the cardiac APD and, therefore, on cardiac arrhythmias vary depending on the method of application, the animal model, and the underlying cardiac pathology.